1998
DOI: 10.1007/s004040050227
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery Doppler velocimetry with leiomyomas

Abstract: The study was conducted to establish a correlation between Doppler velocimetry in relation to uterine weight in any phase of the menstrual cycle and symptoms in women who have leiomyomas. Doppler velocimetry was carried out on both uterine arteries in 18 pre-menopausal women and one post-menopausal woman prior to undergoing abdominal hysterectomy at Winthrop University Hospital in Mineola, NY and at Ioannina University Hospital. The t-test was used for statistical analysis. Changes in flow velocity correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 6 publications
2
14
1
Order By: Relevance
“…Furthermore, women with a uterine volume > 200 cm 3 had significantly higher flow velocities and lower vascular ImIs than those with uterine volume 200 cm 3 . This is similar to the results obtained by Farmakides et al 6 and Alatas et al 5 Leiomyomas with degenerative changes showed higher flow velocities and lower resistance to blood flow in the main uterine artery. This is in agreement with previous studies, 2,26 Abbreviations: 1/PI, Inverse pulsatility index; AI, acceleration index; AT, acceleration time; DAR, diastolic average ratio; DSR, diastolic/systolic ratio; EDV, end-diastolic velocity; ImI, impedance index; PI, pulsatility index; PSV, peak systolic velocity; RI, resistivity index; SDR, systolic-diastolic ratio; TAMX, time-averaged maximum velocity; Tmean, time-averaged mean velocity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, women with a uterine volume > 200 cm 3 had significantly higher flow velocities and lower vascular ImIs than those with uterine volume 200 cm 3 . This is similar to the results obtained by Farmakides et al 6 and Alatas et al 5 Leiomyomas with degenerative changes showed higher flow velocities and lower resistance to blood flow in the main uterine artery. This is in agreement with previous studies, 2,26 Abbreviations: 1/PI, Inverse pulsatility index; AI, acceleration index; AT, acceleration time; DAR, diastolic average ratio; DSR, diastolic/systolic ratio; EDV, end-diastolic velocity; ImI, impedance index; PI, pulsatility index; PSV, peak systolic velocity; RI, resistivity index; SDR, systolic-diastolic ratio; TAMX, time-averaged maximum velocity; Tmean, time-averaged mean velocity.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported increased peak systolic velocity (PSV) and time-averaged maximum velocity (TAMX), as well as diminished pulsatility index (PI), resistivity index (RI), and systolic-diastolic ratio (SDR) in myomatous uteri compared with controls. [2][3][4][5][6] The purposes of this study are: to compare the changes within the main uterine artery of myomatous uteri and normal uteri using several Doppler indices (in addition to the traditional ones); to explore the relationship between these changes in uterine volume and the clinical symptoms; and to compare the main uterine artery Doppler changes in women with recurrent leiomyoma (after a previous myomectomy) and those with primary tumors (without previous surgical or medical intervention).…”
Section: Introductionmentioning
confidence: 99%
“…Previous clinical studies suggested uterine artery blood flow to be important for leiomyoma growth (25). Pharmacological agents such as GnRH analogs (26) and danazol (27), which reduce leiomyoma volume, have been shown to reduce uterine artery blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…They are surrounded by peripheral arteries from which centripetal arteries reach the core of the lesion. Uterine arteries usually enlarge to supply these hypervascular networks 18 . Among the various therapeutic approaches for fibroids such as medical treatment and surgery, the single cathetersingle femoral approach appears to be a safe and cost-effective method to perform embolization of uterine arteries [7][8][9]12 .…”
Section: Discussionmentioning
confidence: 99%